Exploring the anti-aging effects of fisetin in telomerase-deficient progeria mouse model - Zhao, Rui; Kou, Haomeng; Jiang, Duo; Wang, Feng (PeerJ, 2023)
Aging is a natural and complex process characterized by the gradual deterioration of tissue and physiological functions in the organism over time. Cell senescence, a hallmark of aging, refers to the permanent and irreversible cell cycle arrest of proliferating cells triggered by endogenous stimuli or environmental stresses. Eliminating senescent cells has been shown to extend the healthy lifespan. In this study, we established a progeria mouse model with telomerase deficiency and confirmed the presence of shortened telomere length and increased expression of aging markers p16INK4a and p21CIP1 in the organ tissues of G3 Tert-/- mice. We identified fisetin as a potent senolytic drug capable of reversing premature aging signs in telomerase-deficient mice. Fisetin treatment effectively suppressed the upregulation of aging markers p16INK4a and p21CIP1 and reduced collagen fiber deposition. Furthermore, we observed a significant elevation in the mRNA level of Stc1 in G3Tert-/- mice, which was reduced after fisetin treatment. Stc1 has been implicated in anti-apoptotic processes through the upregulation of the Akt signaling pathway. Our findings reveal that fisetin exerts its anti-aging effect by inhibiting the Akt signaling pathway through the suppression of Stc1 expression, leading to the apoptosis of senescent cells.
Keywords: Aging; Telomerase deficient; Senolytics; Fisetin